2022
DOI: 10.3390/app12041908
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Temporal Characteristics of Earthquake Clusters in Selected Areas in Greece

Abstract: The efficiency of earthquake clustering investigation is improved as we gain access to larger datasets due to the increase of earthquake detectability. We aim to demonstrate the robustness of a new clustering method, MAP-DBSCAN, and to present a comprehensive analysis of the clustering properties in three major seismic zones of Greece during 2012–2019. A time-dependent stochastic point model, the Markovian Arrival Process (MAP), is implemented for the detection of change-points in the seismicity rate and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Considering all these points, several tests were carried out with different available catalogues, and it was found that the Aristotle University of Thessaloniki earthquake catalogue (AUTH) [44] was the most suitable for the time period 1995-2022. This database was also previously used in the study conducted by Bountzis et al (2022) to identify seismic clusters in specific regions of Greece [45].…”
Section: Data and Region Analyzedmentioning
confidence: 99%
“…Considering all these points, several tests were carried out with different available catalogues, and it was found that the Aristotle University of Thessaloniki earthquake catalogue (AUTH) [44] was the most suitable for the time period 1995-2022. This database was also previously used in the study conducted by Bountzis et al (2022) to identify seismic clusters in specific regions of Greece [45].…”
Section: Data and Region Analyzedmentioning
confidence: 99%
“…The clustering results provided one relatively large cluster and other small clusters. On the other hand, Bountzis et al [20] present a two step clustering algorithm called the Markovian Arrival Process-(MAP-DBSCAN) to detect change-points in the seismicity rate and subsequently, clustering seismic events in selected areas of Greece. Recently, Sharma [21] proposed two-stage method, based on Self-Organized Map and Density-based Temporal Clustering techniques, for implementing an effective spatiotemporal clustering by identifying the aftershock clusters and background events.…”
Section: Introductionmentioning
confidence: 99%